2018
DOI: 10.3389/fphys.2018.01152
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Nonlinearity of the Movement System to Gestural Theories of Language Use: Multifractal Structure of Spoken English Supports the Compensation for Coarticulation in Human Speech Perception

Abstract: Coarticulation is the tendency for speech vocalization and articulation even at the phonemic level to change with context, and compensation for coarticulation (CfC) reflects the striking human ability to perceive phonemic stability despite this variability. A current controversy centers on whether CfC depends on contrast between formants of a speech-signal spectrogram—specifically, contrast between offset formants concluding context stimuli and onset formants opening the target sound—or on speech-sound variabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…Longrange temporal correlations can be understood as slow "waves" that are reflected by the time series [45,76]. The present results align with the ever growing empirical record of studies that have evidenced the presence and characteristics of long-range correlations and fractal scaling (i.e., a specific pattern of long-range correlations associated with selforganization [42]) in time and trial series of human physiology and performance [40][41][42][43][44][77][78][79][80][81][82][83][84][85][86]. Moreover, the temporal correlations changed over time, indicating multifractality, which is considered a strong indicator for multiplicative interactions across time scales as data-generating process [45].…”
Section: Discussionsupporting
confidence: 84%
“…Longrange temporal correlations can be understood as slow "waves" that are reflected by the time series [45,76]. The present results align with the ever growing empirical record of studies that have evidenced the presence and characteristics of long-range correlations and fractal scaling (i.e., a specific pattern of long-range correlations associated with selforganization [42]) in time and trial series of human physiology and performance [40][41][42][43][44][77][78][79][80][81][82][83][84][85][86]. Moreover, the temporal correlations changed over time, indicating multifractality, which is considered a strong indicator for multiplicative interactions across time scales as data-generating process [45].…”
Section: Discussionsupporting
confidence: 84%
“…Multifractality is a measure of system complexity, developed in fluid mechanics, but now important in a range of fields [47], including physiology [6,34,55,75,83] and cognitive science [32,44,52,76]. Multifractality indicates the role of complex nonlinear interactions in a system's behaviour [42,52], and a large literature now demonstrates its presence in a wide range of human behaviours [15,16,23,33,35,46,57,65,76,77,84], often associated with adaptive flexibility [4,56,67].…”
Section: Multifractalitymentioning
confidence: 99%
“…Multifractal nonlinearity moderates all influences of task constraints and intentional control on cascade dynamics. Indeed, extensive research has shown that multifractal nonlinearity of upright posture changes in response to task constraints [57] and intentions [58], and changes in multifractal nonlinearity influences participants’ perceptual judgments [53,59,60]. In the present case, we hypothesize that multifractal nonlinearity would shape all features articulated above: the scale-dependent cascade carrying the reactive response to destabilization, the scale-invariant cascade carrying proactive stabilization specifically under destabilizing task constraints, and the reconfiguration of cascade dynamics supporting intentional resetting of equilibrium points in general (Hypothesis-4).…”
Section: Introductionmentioning
confidence: 99%